2021
DOI: 10.3390/su132313036
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Education in Sustainable Dietary Patterns in Slovenia

Abstract: The most sustainable dietary patterns involve the consumption of plant-based (vegan) foods, excluding or reducing animal products, including meat, fish, and dairy, yet there is a lack of research on determinants of sustainable dietary patterns in central European countries. The present article aimed to examine the prevalence of sustainable dietary practices and attitudes among the Slovenian public and to investigate the role of education in fostering sustainable dietary patterns. We analyzed a representative n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Higher levels of educational attainment were associated more with the “vegetable-focused” diet and less with a “meat-focused” dietary pattern. These results mirror previous studies that found that persons with a higher level of educational attainment consumed less meat and more vegetables [ 78 , 79 ]. In terms of household composition, it was found that households without children were more likely to be in the “vegetable-focused” group.…”
Section: Discussionsupporting
confidence: 90%
“…Higher levels of educational attainment were associated more with the “vegetable-focused” diet and less with a “meat-focused” dietary pattern. These results mirror previous studies that found that persons with a higher level of educational attainment consumed less meat and more vegetables [ 78 , 79 ]. In terms of household composition, it was found that households without children were more likely to be in the “vegetable-focused” group.…”
Section: Discussionsupporting
confidence: 90%
“…In other countries, the level of education also influenced meat consumption. A Slovenian study showed that the education level had an impact on the frequency of meat consumption and sustainability attitudes; a higher educational level was an independent predictor of lower meat consumption [ 52 ]. In Germany, consumers characterised by a higher educational level more often reduced meat consumption than people with a lower educational level [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is also clearly shown in the present study, in which the large variation (i.e., in terms of standard deviation of CF) within the same food category reflects the effect of single food choices on environmental impact. It should be considered that dietary choice is the result of numerous determinants, and attitudes towards sustainability have been reported to be influenced by gender, location of residence (region and urban vs. non-urban), social class, age, and education [ 27 , 28 ]. For instance, a German nutritional survey on meat consumption carried out in 2019 found that non-meat consumers do not substitute meat with fish, eggs, or milk products but rather with soya products and other plant-based foods.…”
Section: Discussionmentioning
confidence: 99%